Modern Hindu traditionalism in contemporary India : Śrī Math and the Jagadguru Rāmānandācārya in the evolution of the Rāmānandī sampradāya - Bevilacqua, Daniela (Routledge Hindu studies series, 2018)
"Modern Hindu Traditionalism addresses Hindu traditions that resisted contact with both Neo-Hindu thought and views of 'classical' Hinduism perceived to be outmoded. This books provides an in-depth understanding of Modern Hindu Traditionalism through the case study of the Ramanandi order (sampradaya) and the portrait of the Jagadguru Ramanandacarya Ramnaresacarya. This guru belongs to the ancient tradition of the Ramanandi order, which is active at the present time and the biggest Vai'ava religious order in Northern India. Analysing the historical evolution of the Ramanandi order, the author shows how different centres have undergone different changes over the centuries, and focuses on the independence struggle of a group of Ramanandis from the Ramanujis, which led to the creation of the role of Jagadguru Ramanandacarya and the construction of the Śrī Math. Drawing on extensive fieldwork, this book casts light on figures and processes central to the development of Hinduism in the 20th and 21st century and consequently describes the role of religion in contemporary Indian society. The author examines the role religious institutions and their leaders have in the everyday life of individuals, how they interact with and in the society, and how they approach and interpret social and political issues. The Ramanandis' use of new methods of communication, in particular social media, is an innovative part of the study. A welcome innovation in the studies of South Asian religion, this book will be of interest to historians, anthropologists and scholars of Hinduism and religion and politics"--